Electron Concentration Dependence of Phase Transition and Magnetic Properties in NiMnGa Alloys - Kok, Mediha; Aydogdu, Yildirim (Springer, 2013)
The phase transition, Curie temperature and magnetic properties of NiMnGa alloys represented by S1, S2, S3, and S4 in different atomic percentage were investigated from TG/DTA and PPMS measurements. It was found that the electron concentration (e/a) ratio of S1 and S4 as well as S2 and S3 are equal to each other. The transformation temperatures and magnetization values are similar for these alloys having the same e/a. Results show that room temperature magnetization depends on valence electron concentration of alloys and saturation of alloys increases with the decrease of e/a ratio. The measured coercivity values for all alloys were above 125 Oe and they had a long saturation field, i.e., above 10000 Oe, by exhibiting, the characteristics of hard magnetic materials.
Keywords: Electron concentration; NiMnGa; Phase transition; Magnetic property